2017
DOI: 10.3390/rs9040324
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Patterns of Transmitted Celestial Light under Wavy Water Surfaces

Abstract: This paper presents a model to describe the polarization patterns of celestial light, which includes sunlight and skylight, when refracted by wavy water surfaces. The polarization patterns and intensity distribution of refracted light through the wave water surface were calculated. The model was validated by underwater experimental measurements. The experimental and theoretical values agree well qualitatively. This work provides a quantitative description of the repolarization and transmittance of celestial li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…As depth increases, multi-path scattering destroys the pattern coming from the sky and only in-water scattering, produced near the observer, remains. At very low depth, the influence of wavy water surfaces on the polarization pattern has been simulated and measured [ 264 ]. It was revealed that the wind speed also has an influence on the pattern.…”
Section: Polarized Vision For Robotics Navigationmentioning
confidence: 99%
“…As depth increases, multi-path scattering destroys the pattern coming from the sky and only in-water scattering, produced near the observer, remains. At very low depth, the influence of wavy water surfaces on the polarization pattern has been simulated and measured [ 264 ]. It was revealed that the wind speed also has an influence on the pattern.…”
Section: Polarized Vision For Robotics Navigationmentioning
confidence: 99%
“…In recent years, domestic scholars have also started to investigate underwater polarized light. in 2017, Zhou [21] In 2020, Cheng [22] et al also combined the Monte Carlo numerical simulation approach with the Mie scattering theory to simulate the multiple scattering of suspended particles underwater and modelled the polarization distribution in turbid water within the Snell window. The maximum depth at which the polarization distribution pattern can be stably kept under distinct types of water quality is also calculated, and the effects of turbidity, wavelength, type of suspended matter and particle size on the underwater polarization distribution pattern are discussed.…”
Section: Analytical Model Of Underwater Polarization Patternsmentioning
confidence: 99%
“…Sabbah et al [5] considered the water interface refraction to simulate the underwater polarization pattern based on the Mueller matrix and Stokes vector. Some researchers discussed the effect of wavy water surface [10], water molecules [11], suspended particles [12], and other various factors [13] on the underwater polarization patterns. You et al [14] developed a hybrid of the matrix operator and Monte Carlo radiative transfer models to predict the polarized light field.…”
Section: Introductionmentioning
confidence: 99%